Indoor blind navigator: A use case for self-guided tours in museums - Meliones, A.; Sampson, Demetrios (2017)
© 2017 ACM. Notably valuable efforts have focused in helping people with special needs. In this work, we build upon the experience from the BlindHelper smartphone outdoor pedestrian navigation app and present Blind Nav , a system for indoor interactive autonomous navigation of blind and vision-impaired persons and groups (e.g. pupils) in museums. A pilot prototype is under development with the collaboration of the Lighthouse for the Blind of Greece. The paper describes the functionality of the application and evaluates candidate indoor location determination technologies, such as WLAN, Zigbee, and assistive tactile route indications combined with Bluetooth beacons and distance and direction change metering functionality, to come up with a reliable indoor positioning system adopting the latter solution.